Newspaper cartoons as a reflection of political change during the first democratic elections in South Africa - Cornelius van Heerden (Communicare)
The first Southern African cartoonists were probably the Stone Age Bushman whose drawings adorn rock faces in this part of the continent. Modern cartoonists may use more sophisticated equipment but their drawings, although on recyclable print, also reflect a particular part of our history. The following view of Schoonraad et al (1989:15: "A collection of cartoons covering a particular period, will present an unequalled graphic history of political and current events" They also add that the state of any nation is reflected by its newspaper cartoons Geipel 1972 argues that to the historian, cartoons represent priceless primary source of information about fleeting modes and morals of the passing generations. Few commentators Pretoria will disagree that the run-up to the 1994-election can be regarded as one of the most crucial moments in South African history. The focus will only be on the editorial cartoon usually found on the centre pages of Sunday and daily newspapers and not on comic strips of which the majority are from US-syndications. The only local comic strips that provide (198 social and political commentary are "Ben, Babsie en Famille" and "Louis die Laeveld Leeu".